Molecular Docking, Bioinformatic Analysis, and Experimental Verification for the Effect of Naringin on ADHD: Possible Inhibition of GSK-3β and HSP90 - Hatem I. Mokhtar; Sawsan A. Zaitone; Karima El-Sayed; Rehab M. Lashine; Nada Ahmed; Suzan M. M. Moursi; Shaimaa A. Shehata; Afaf A. Aldahish; Mohamed A. Helal; Mohamed K. El-Kherbetawy; Manal S. Fawzy; Noha M. Abd El-Fadeal (Pharmaceuticals)
Background/Objectives: One of the most abundant and growing neurodevelopmental disorders in recent decades is attention deficit hyperactivity disorder (ADHD). Many trials have been performed on using drugs for the improvement of ADHD signs. This study aimed to detect the possible interaction of naringin with Wnt/β-catenin signaling and its putative anti-inflammatory and protective effects in the mouse ADHD model based on bioinformatic, behavioral, and molecular investigations. Furthermore, molecular docking was applied to investigate possible interactions with the GSK-3β and HSP90 proteins. Methods: Male Swiss albino mice were divided into four groups, a normal control group, monosodium glutamate (SGL) control, SGL + naringin 50 mg/kg, and SGL + naringin 100 mg/kg. The psychomotor activity of the mice was assessed using the self-grooming test, rope crawling test, and attentional set-shifting task (ASST). In addition, biochemical analyses were performed using brain samples. Results: The results of the SGL group showed prolonged grooming time (2.47-folds), a lower percentage of mice with successful crawling on the rope (only 16.6%), and a higher number of trials for compound discrimination testing in the ASST (12.83 ± 2.04 trials versus 5.5 ± 1.88 trials in the normal group). Treatment with naringin (50 or 100 mg per kg) produced significant shortening in the grooming time (31% and 27% reductions), as well as a higher percentage of mice succeeding in crawling with the rope (50% and 83%, respectively). Moreover, the ELISA assays indicated decreased dopamine levels (0.36-fold) and increased TNF-α (2.85-fold) in the SGL control group compared to the normal mice, but an improvement in dopamine level was observed in the naringin (50 or 100 mg per kg)-treated groups (1.58-fold and 1.97-fold). Similarly, the PCR test showed significant declines in the expression of the Wnt (0.36), and β-catenin (0.33) genes, but increased caspase-3 (3.54-fold) and BAX (5.36-fold) genes in the SGL group; all these parameters were improved in the naringin 50 or 100 mg/kg groups. Furthermore, molecular docking indicated possible inhibition for HSP90 and GSK-3β. Conclusions: Overall, we can conclude that naringin is a promising agent for alleviating ADHD symptoms, and further investigations are required to elucidate its mechanism of action.